Switching off malignant pleural effusion formation—fantasy or future? - Spella, Magda (J Thorac Dis, 2015)
Malignant pleural effusion (MPE) is common and difficult to treat. In the vast majority of patients the presence of MPE heralds incurable disease, associated with poor quality of life, morbidity and mortality. Current therapeutic approaches are inefficient and merely offer palliation of associated symptoms. Recent scientific progress has shed light in the biologic processes governing the mechanisms behind the pathobiology of MPE. Pleural based tumors interfere with pleural fluid drainage, as well as the host vasculature and immune system, resulting in decreased fluid absorption and increased pleural fluid production via enhanced plasma extravasation into the pleural space. In order to achieve this feat, pleural based tumors must elicit critical vasoactive events in the pleura, thus forming a favorable microenvironment for tumor dissemination and MPE development. Such properties involve specific transcriptional signaling cascades in addition to secretion of important mediators which attract and activate host cell populations which, in turn, impact tumor cell functions. The dissection of the biologic steps leading to MPE formation provides novel therapeutic targets and recent research findings provide encouraging results towards future therapeutic innovations in MPE management.